2011
DOI: 10.3109/09513590.2011.632791
|View full text |Cite
|
Sign up to set email alerts
|

The vascular endothelial growth factor (VEGF) polymorphisms and the risk of endometriosis in northern Iran

Abstract: Vascular endothelial growth factor (VEGF) is known to be a key molecule in the pathogenesis of endometriosis. In this study, we evaluated whether two polymorphisms -460T>C and +405G>C in VEGF are related with the susceptibility to endometriosis in northern Iran. Genomic DNA derived from patients with endometriosis and healthy women were analysed by polymerase chain reaction-restriction fragment length polymorphism. The total number of 1080 subjects (480 patients with endometriosis and 600 normal controls) was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(35 citation statements)
references
References 26 publications
1
29
0
5
Order By: Relevance
“…Thus far, there are reports of no association of VEGF -460 C/T in Northern Iran and of VEGF +405 G/C in samples from all Iranian populations (23,24). Additionally, no contribution of the +936 C/T SNP with endometriosis in Korean females has been observed (25).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Thus far, there are reports of no association of VEGF -460 C/T in Northern Iran and of VEGF +405 G/C in samples from all Iranian populations (23,24). Additionally, no contribution of the +936 C/T SNP with endometriosis in Korean females has been observed (25).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, no contribution of the +936 C/T SNP with endometriosis in Korean females has been observed (25). However, the +405 G/C VEGF polymorphism has been associated with a higher susceptibility of endometriosis in Northern Iran, Turkish, South Indian, Italian and Korean females (23,(26)(27)(28)(29)43). Bhanoori et al (44) demonstrated that the -460T/+405C haplotype of VEGF was less frequently identified in females with endometriosis compared to the controls, and VEGF -460 T/T homozygotes and the T allele are associated with a higher risk of endometriosis in Chinese females.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In recent years, several published articles indicated that the vascular endothelial growth factor (VEGF) is one of the most important candidate genes for the development of endometriosis, and genetic polymorphisms in VEGF gene might be potentially associated with the risk of endometriosis. [3][4][5][6][7][9][10][11][12][13][14][15][16][17][18][19][20] The þ405G>C genetic polymorphism in 5 0 -untranslated region of VEGF gene (rs2010963), one of the most studied genetic variants resulting from G to C mutations, has been reported to affect on the regulation of VEGF gene expression and contributed to the risk of endometriosis in diverse populations. [3][4][5][6][7][9][10][11][12][13][14][15][16][17] However, findings from these published articles were conflicting but not conclusive.…”
Section: Introductionmentioning
confidence: 99%